2017
DOI: 10.1021/acscatal.6b03661
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed β-C–H Arylation of Alkyl Carboxamides with Sterically Hindered Aryl Iodides Using ortho-Sulfinyl Aniline Auxiliaries

Abstract: We disclose a pair of ortho-sulfinylaniline auxiliaries for palladium-catalyzed β–C-H arylation of alkyl carboxamides. Together, these auxiliaries offer a means to effect efficient β-methyl and methylene C–H bond arylation with sterically hindered aryl iodides. ortho-Methylsulfinylaniline (MSOA) enables efficient β-methyl C–H arylation of propanamide substrates with aryl iodides bearing various ortho-substituents including alkyl groups. ortho-Tosylsulfinylaniline (TSOA) enables β-methylene C–H arylation with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Based on this pioneering work and targeting a new asymmetric approach towards direct functionalization of linear alkanes, we report herein a diastereoselective C−H arylation of aliphatic substrates using ( S )‐2‐( p ‐tolylsulfinyl)aniline (APS) as a chiral auxiliary and precursor of a bicoordinating directing group. During the preparation of this manuscript, a closely related bicoordinating DG has been employed for direct arylation of aliphatic substrates, however, the stereoselective outcome of such transformation was just mentioned in one example …”
Section: Figurementioning
confidence: 97%
See 3 more Smart Citations
“…Based on this pioneering work and targeting a new asymmetric approach towards direct functionalization of linear alkanes, we report herein a diastereoselective C−H arylation of aliphatic substrates using ( S )‐2‐( p ‐tolylsulfinyl)aniline (APS) as a chiral auxiliary and precursor of a bicoordinating directing group. During the preparation of this manuscript, a closely related bicoordinating DG has been employed for direct arylation of aliphatic substrates, however, the stereoselective outcome of such transformation was just mentioned in one example …”
Section: Figurementioning
confidence: 97%
“…Regrettably, replacement of the silver salt by potassium or cesium carbonate resulted in an inhibition of the reaction (Table , entries 9, 10). Likewise, significantly inferior results in terms of either efficiency or stereoselectivity were obtained using pivalic acid or potassium fluoride additives, respectively (Table , entries 11, 12), reaction conditions inspired from the recent work of Chen and He . Although this aim of this optimization study was to establish a protocol allowing high reactivity for such a challenging C(sp 3 )−H activation at methylene position, it also clearly shows that regardless of the conditions used, only modest diastereoselectivity (typically 3:2) could be achieved.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, ortho ‐tolylsulfinyl aniline (TSOA, TA8 ) showed much lower reactivity. In our previous study, we have shown that these two ortho ‐sulfinyl aniline auxiliary group are particularly effective at facilitating Pd‐catalyzed β‐C(sp 3 )‐H arylation of the corresponding alkyl carboxamides with sterically hindered aryl iodides …”
Section: Methodsmentioning
confidence: 99%